Revitalizing Orange Products: Implementation of Appropriate Technology for Higher Market Value - Subiyantoro, Edi; Santi, Fitriana; Tsamroh, Dewi Izzatus; Wea, Efrida; Mutadafiq, Fiqih Syahdani (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2024)
Oranges have a short shelf life, requiring immediate sale or processing to maintain their market value. Gading Kulon Village in Malang Regency has fertile land, making it a potential area for citrus picking tourism. The phenomenon of abundant harvests every season causes tour operators to incur losses due to plummeting prices. Unsold oranges are given away for free, leading to minimal profits for the tour operators. The objective of this community service is to increase the selling price of products by processing oranges into candies. Efficient processing requires appropriate technology, facilitating tour operators in meeting consumer demands. The community service method involves training and product trials. The results of the community service demonstrate the enthusiasm of the women processing oranges in turning them into candies.